RASIONALITAS KONSUMSI PETANI MUSLIM PADA DESA SUMBER KABUPATEN PROBOLINGGO DALAM PERSPEKTIF ISLAM - M. Alvian Arfiliananda; Atina Shofawati (Universitas Airlangga, 2018)
The aim of the study is to know the Consumption Rationality of Moslem Farmer in Sumber Village, Probolinggo District in Islamic perspective. The method used case study with qualitative descriptive approach. This study is using interview for primary data. This study scope focus is limited to moslem farmer in Sumber Village, Probolinggo District who has their own farmland. In this study, consumption preference theory in Islam is used as a scope to search answers on how is the rationality consumption of moslem farmer in sumber village Probolinggo District in Islamic perspective. The results obtained were how Moslem Farmer in Sumber Village, Probolinggo District consumption is in accordance with the consumption rationality in Islam. It is proven by the balance between mundane (duniawi) consumption with the afterlife, and how the necessity fulfilled suits consumption principal in Islam. REFERENCESAnto, Hendrie MB. 2003. Pengantar Ekonomika Mikro Islami. Yogyakarta:EKONISIA.Baidhowi, Bagus. 2014. Implementasi Konsumsi Islam pada Pengajar Pondok Pesantren . Universitas Airlangga Surabaya.Dagun, Save M. 1992. Pengantar Filsafat Ekonomi. Jakarta:Rineka Cipta.Halim, Abdul. 2014. Analisis Komparatif terhadap Konsep Konsumsi dalam Pandangan Ekonomi Islam dan Ekonomi Konvensional. Jakarta.Huda, Nurul. 2006. Konsep Perilaku Konsumsi dalam Ekonomi Islami. ISSN.Logati, Anggraini. 2011. Rasionalitas Konsumsi Keluarga Muslim Beranak Banyak Perspektif Maqashid Syariah. Universitas Airlangga Surabaya.Moleong, Lexy J. 2014. Metodologi Penelitian Kualitatif. Edisi Revisi. Bandung:Remaja Rosdakarya.Muhammad. 2004. Ekonomi Mikro dalam Perspektif Islam.Yogyakarta:BPFE-Yogyakarta.Pusat Data dan Sistem Informasi Pertanian.2014. Analisis Data Kesejahteraan Petani 2014, (online), (http://pusdatin.setjen.pertanian.go.id/tinymcpuk/gambar/file/Analisis_Kestan_2014.pdf, diakses 11 Januari 2017).Suwiknyo, Dwi. 2010. Kompilasi Tafsir Ayat-ayat Ekonomi Islam. Yogyakarta:Pustaka Pelajar.Sukino. 2013. Membangun Pertanian dengan Pemberdayaan Masyarakat Tani (terobosan menanggulangi kemiskinan). Yogyakarta:Pustaka Baru Press.Suyanto, Bagong. 2013. Sosiologi Ekonomi. Jakarta:Kencana